2019
DOI: 10.21106/ijma.273
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Obesity Among School-aged Children and Maternal Preventive Practices against Childhood Obesity in Select Local Government Areas of Lagos, Southwest, Nigeria

Abstract: Background: Childhood obesity is an emerging epidemic in the developing countries, particularly in the urban settings. This study examines the prevalence of overweight and obesity among school-aged children and the maternal preventive practices against childhood obesity. Methods: This is a cross-sectional study of school-aged children aged 6-13 years and mothers from two Local Government Areas of Lagos State, Southwest Nigeria. Multi-stage sampling technique was used to select study areas and participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…81 Although the majority of this burden falls on older Nigerians, evidence suggests that cardiometabolic risk factors are occurring at increasingly earlier ages. 104,105 As such, the risk factors for cardiometabolic disease need to be addressed at younger ages, not later, as is commonly believed. As the Nigerian population continues to grow, the relationship between the population and the environment will be increasingly important.…”
Section: Environmental and Cardiometabolic Risk Factorsmentioning
confidence: 99%
“…81 Although the majority of this burden falls on older Nigerians, evidence suggests that cardiometabolic risk factors are occurring at increasingly earlier ages. 104,105 As such, the risk factors for cardiometabolic disease need to be addressed at younger ages, not later, as is commonly believed. As the Nigerian population continues to grow, the relationship between the population and the environment will be increasingly important.…”
Section: Environmental and Cardiometabolic Risk Factorsmentioning
confidence: 99%
“…[4,5] Obesity has been associated with risk factors: high parental body mass index, high income, low parental education, poor dietary habits, inadequate sleep, sedentary behaviour, and increased time spent viewing screens such as television and video games. [5][6][7][8][9][10] It is known that increased food intake in general, and fat-rich diets and high-calorie intake in particular, raise the risk of overweight and obesity. [5,6] Even though the effect of fruits and vegetables on overweight and obesity in children and adolescents has not been sufficiently studied, there are reports that inadequate intake of fresh fruits and vegetables are associated with weight gain and the development of obesity.…”
Section: Annals Of Health Research Volume 8 Issue No 1 2022__________...mentioning
confidence: 99%
“…[2] Previous research conducted in Nigeria has demonstrated the prevalence of overweight and obesity across a range of population strata, including adults, [3][4][5][6][7][8] adolescents [9,10] and children. [11,12] A collection of disorders that impact how the body uses blood sugar are together referred to as diabetes mellitus (DM). [13] Insulin production or usage problems lead to type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%